YAP signaling induces PIEZO1 to promote oral squamous cell carcinoma cell proliferation. Issue 1 (5th November 2020) - Hasegawa, Kana; Fujii, Shinsuke; Matsumoto, Shinji; Tajiri, Yudai; Kikuchi, Akira; Kiyoshima, Tamotsu
Abstract: Most cancer cells are exposed to altered extracellular environments, such as an increase in extracellular matrix (ECM) stiffness and soluble signals consisting of growth factors and cytokines. It is therefore conceivable that changes in tumor extracellular environments affect tumor cell behavior. The Hippo pathway reportedly responds to the extracellular environment and regulates the nuclear localization of the transcription co‐activator, yes‐associated protein (YAP)/transcriptional co‐activator with PDZ‐binding motif (TAZ). Inactivation of the Hippo pathway with nuclear translocation of YAP/TAZ stimulates cell proliferation. Its pathway also regulates gene expression, but the precise molecule(s) meditating the cell‐proliferating effect of YAP signaling on oral squamous cell carcinoma (OSCC) is unclear. First, we examined the effects of YAP signaling on OSCC tumorigenesis. Loss‐of‐function experiments using siRNA or an inhibitor, and immunohistochemical analyses of tissue specimens obtained from OSCC patients demonstrated that YAP signaling was involved in OSCC cell proliferation. Second, we identified Piezo‐type mechanosensitive ion channel component 1 (PIEZO1), a Ca 2+ channel, as a transcriptional target of YAP signaling and showed that elevated PIEZO1 was required for PIEZO1 agonist‐dependent Ca 2+ entry and cell proliferation in OSCC cells. Experiments using three‐dimensional and suspension culture revealed that PIEZO1 was involved in OSCC cellular growth. Finally, YAP overexpression in the nucleus and/or cytoplasm was immunohistochemically detected in tumor lesions with frequent expression of both PIEZO1 and Ki‐67, but not in non‐tumor regions of OSCC specimens. These results suggest that the YAP/PIEZO1 axis promotes OSCC cell growth. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.